2012
DOI: 10.1523/jneurosci.3974-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Neural Processing and Somatosensory Awareness

Abstract: The neural mechanisms of stimulus detection, despite extensive research, remain elusive. The recurrent processing hypothesis, a prominent theoretical account of perceptual awareness, states that, although stimuli might in principle evoke feedforward activity propagating through the visual cortex, stimuli that become consciously detected are further processed in feedforward-feedback loops established between cortical areas. To test this theory in the tactile modality, we applied dynamic causal modeling to elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 51 publications
14
82
0
Order By: Relevance
“…Accuracy of tactile discrimination was significantly correlated with measures of network activity in both bands. These results provide direct evidence of recurrent information processing of sensory and attentional signals as in somatosensory awareness (Auksztulewicz et al, 2012) and in other forms of decision-making (Klein-Flugge and Bestmann, 2012; Selen et al, 2012). These findings, together with previous studies in the visual (Siegel et al, 2011) and auditory-visual domains (Hipp et al, 2011) suggest common oscillatory network mechanisms for perceptual decision-making across various sensory modalities.…”
Section: Discussionmentioning
confidence: 67%
“…Accuracy of tactile discrimination was significantly correlated with measures of network activity in both bands. These results provide direct evidence of recurrent information processing of sensory and attentional signals as in somatosensory awareness (Auksztulewicz et al, 2012) and in other forms of decision-making (Klein-Flugge and Bestmann, 2012; Selen et al, 2012). These findings, together with previous studies in the visual (Siegel et al, 2011) and auditory-visual domains (Hipp et al, 2011) suggest common oscillatory network mechanisms for perceptual decision-making across various sensory modalities.…”
Section: Discussionmentioning
confidence: 67%
“…Dynamic long-range phase synchrony is also enhanced when visual stimuli are consciously seen (14,22,50). Importantly, recurrent rather than feed-forward interactions have been implicated in conscious perception (8,51), and such interactions may reflect a process of convergence toward a transiently stable state (9). The notion of transient stability (or metastability) has been invoked in many theoretical accounts of conscious sensory perception (9,11,13,15,37,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recurrent neural activity in the somatosensory hierarchy has previously been shown to be important for conscious somatosensory awareness (Auksztulewicz et al 2012); in general such cortical-subcortical loops are thought to be critical for conscious awareness (Dehaene et al 2014). Here we found that strong recurrent connectivity between the AIC and somatosensory cortex supports the processing of tactile oddballs, and that individual differences in the strength of backwards influences from the PFC to AIC predicted the self-rated ease of detecting subtle stimulus changes.…”
Section: Discussionmentioning
confidence: 99%
“…Somatosensation underlies the conscious body-image that underpins body-ownership and action agency (Serino and Haggard 2010) and has recently been shown to rely on hierarchical Bayesian inferences (Auksztulewicz et al 2012;Ostwald et al 2012). The AIC is richly interconnected with the posterior insula and somatosensory cortex (Cerliani et al 2012;Chang et al 2012), and anticipates the sensory and affective consequences of touch (Lovero et al 2009).…”
Section: Introductionmentioning
confidence: 99%